Strategies of fibre network operators to address increasing competition and decreasing investment output in the South African fibre to the home market - Tsoana, Molefe Donald (University of the Witwatersrand, Johannesburg, 2023)
The deployment of high-speed networks and connectivity technologies has evolved quickly from the past. From Copper infrastructure, Digital Subscriber Line (“x”DSL) technologies, namely; Asymmetric Digital Subscriber Line (ADSL), Very-high-bit- rate Digital Subscriber Line (VDSL), and High-speed Digital Subscriber Line (HDSL) (Jenkinson, 2000). The “x”DSL face out started in about 2007 when Telkom South Africa (SA) started rolling out optical fibre distribution network (ODN) in SA. Passive Optical Network (PON) infrastructure is the most popular and adopted optical distribution network, globally. It is through this technology that the household broadband connectivity, fibre-to-the-home (FTTH) is enabled (Keiser, 2006). While there is still an existing concern of the considerable digital divide in SA. The FTTH connectivity is one of the basic utility needs for most families. It is considered a potential driver for micro and macro-economic growth in Africa. As this seems an opportunity for infrastructure investment, the number of FNOs in the SA FTTH market has recently risen to over 38 while the cream of the crop areas are almost fibre saturated, making the FTTH market share competition very stiff. The motivation for this research from an academic perspective, is to add on to the existing body of knowledge regarding FTTH broadband service in SA. To study strategies of FNOs to address increasing competition and decreasing investment output in the SA FTTH market. This research also aims to study the; value-added services, customer value propositions (CVPs) and innovations implemented by these FNOs to stay competitive and sustainable, as well as to better their FTTH investment output. The evolution of the FTTH service is SA has proven to be challenging to most FNOs, and it has been evident post Covid-19 pandemic that pricing can never be a dependable differentiator thus the need for innovative offerings in order to combat an increasing market competition, to better their investment output
A research project submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, [2023]
Keywords: FNOs; FTTH; Market competition; Investment output; Innovation; Differentiator; Valued-added services; Competitive edge; Competitive advantage; UCTD; SDG-8: Decent work and economic growth